2016
DOI: 10.2903/j.efsa.2016.4398
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of selenium compounds (E8) as feed additives for all animal species: sodium selenite, based on a dossier submitted by Retorte GmbH Selenium Chemicals and Metals

Abstract: Selenium is a trace element that is essential for vertebrates and involved in a series of vital metabolic functions. Sodium selenite is considered to be a safe and efficacious source of selenium for all animal species/categories. The use of sodium selenite as a source of selenium in animal nutrition is considered to be safe for the consumer, provided that the total maximum authorised content of selenium in complete feed is respected. The additive is considered to be an irritant to the skin, eyes and the respir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…In previous opinions, the FEEDAP Panel assessed the safety for the environment of the inorganic source of sodium selenite when used in animal nutrition up to the maximum authorised content in feed and concluded that not concerns to the environment were expected (EFSA FEEDAP Panel, 2015, 2016a. The additive under assessment, sodium selenate for use in complementary feed for ruminants in the form of ruminal boluses, is intended to be a substitute for other authorised selenium additives and will not further increase the environmental burden of selenium.…”
Section: Safety For the Environmentmentioning
confidence: 99%
“…In previous opinions, the FEEDAP Panel assessed the safety for the environment of the inorganic source of sodium selenite when used in animal nutrition up to the maximum authorised content in feed and concluded that not concerns to the environment were expected (EFSA FEEDAP Panel, 2015, 2016a. The additive under assessment, sodium selenate for use in complementary feed for ruminants in the form of ruminal boluses, is intended to be a substitute for other authorised selenium additives and will not further increase the environmental burden of selenium.…”
Section: Safety For the Environmentmentioning
confidence: 99%
“…The toxicology of selenium, including organic forms, namely SeMet, has been extensively reviewed by the Scientific Committee on Food (SCF) (European Commission, 2000), the Agency for Toxic Substances and Disease Registry (ATSDR, 2003), the WHO (2011), the European Medicines Agency (EMA, 2015) and the FEEDAP Panel (EFSA, 2006(EFSA, , 2009EFSA FEEDAP Panel, 2011b,c, 2013a,b, 2014a,b, 2015, 2016a.…”
Section: Toxicological Studiesmentioning
confidence: 99%
“…The FEEDAP Panel has already adopted two opinions on sodium selenite in the frame of re-evaluation (EFSA FEEDAP Panel, 2015, 2016.…”
Section: Additional Informationmentioning
confidence: 99%
“…Symptoms of deficiency and toxicosis of selenium are described in detail in previous opinions of the FEEDAP Panel (EFSA, 2006;EFSA FEEDAP Panel, 2011b, 2016 and scientific reviews (e.g. McDowell, 2003;Suttle, 2010).…”
Section: Safety For the Target Speciesmentioning
confidence: 99%
See 1 more Smart Citation